Miejsca kultury w antropologii i etnografii edukacyjnej - Hana Červinková; Tomasz Woźniak (Problemy Wczesnej Edukacji)
The focus of this article is on culture as a central concept of educational anthropology – a subdiscipline of anthropology that focuses on the fields of education and learning as key aspects of social life. It begins with an introduction into how culture has been criticially conceptualized in anthropology and ethnography and then illustrates how educational anthropologists have used the concepts of culture and cultural critique to analyze educational processes in diverse sociocultural settings. The author points out three primary areas in which anthropology of education enriches our understanding of education and learning: 1) investigations of diversity of educational practices in different sociocultural contexts; 2) critical examination of cultural practices and structures of inequality and exclusion vis-à-vis minority subjects in the educational process; 3) positioning of participatory research approaches and engagement as legitimate methodological and scholary standpoints. The article builts primarily on examples of texts that have been recently published in the Polish language in order to help situate the perspective of educational anthropology in Polish scholarly discourse and tradition.